Karakteristik Organoleptik Dan Fisikokimia Minuman Fungsional Ekstrak Kulit Buah Mangga Golek dengan Penambahan Ekstrak Jahe Merah Dan Madu - Hapsari, Distya Riski; Indrastuti, Nindya Atika; Pratiwi, Namira Indah (JURNAL AGROINDUSTRI HALAL, 2024)
Mango golek is one of the superior varieties in Indonesia. Utilization of local varieties of mango peel in a fresh form as raw material for functional drinks is not yet available. This study aims to develop ripe mango peel into a ready-to-drink functional beverage product with the addition of red ginger extract and rambutan honey which aims to improve the functional and sensory properties of mango peel extract as an effort to diversify food. The experimental design used a one factor Completely Randomized Design (CRD) with three treatment levels (mango peel extract: red ginger extract: rambutan honey) namely A0 (100%: 0%: 0%), A1 (85%: 10%:5%), and A2 (75%:15%:10%). The analysis included organoleptic tests (sensory and hedonic quality), physical tests (total dissolved solids and pH), and chemical tests (antioxidant activity and total phenol). The decreased levels of mango golek peel extract as well as increase of red ginger and rambutan honey gave a tendency to increased the value of sensory, hedonic quality, total soluble solids, antioxidant activity and total phenol but gave a tendency to decrease the pH value of functional drinks. Selected product of functional drinks based on mango golek peel extract was A2 had a sensory quality of orange color (6.84), uncharacteristic aroma of mango peel (5.50), uncharacteristic taste of mango peel (5.48), non-bitter aftertaste (6.93), turbid appearance (3.35) and uncharacteristic overall of mango peel (5.83) and had a very high level of hedonic preference with a score of 6.18-6.99. The selected formula had a total dissolved solids value of 10.6°Brix; pH 4.83; antioxidant activity 51.07% and total phenol 0.48 mg GAE/g.